Development of Zoonotic Diseases at the Convergence of Wildlife-Livestock System: A Systematic Review - Dhananjay Kumar Yadav, Chhaya Agarwal, Bhuvana Jayabalan (Revista Electronica de Veterinaria, 2024)
Zoonotic diseases are a major danger in worldwide public health because they originate at the interface between animal and cattle systems. Effective disease control in cattle and poultry requires an understanding of the origins and hazards of infections. Since the human-animal interface is where the majority of illnesses originate, it is imperative to comprehend the unique processes and motivations at play to be ready for any future epidemics. The rise of zoonotic illnesses is attributed to interactions between livestock and wildlife systems, particularly about globalization, habitat degradation, fragmentation, as well as climate change. This comprehensive review investigates the complex mechanisms that contribute to the establishment and spread of zoonotic illnesses in the integration of wildlife-livestock systems. To monitor zoonotic illnesses, we want to determine the sources of infections in cattle and poultry to evaluate the risks of zoonotic transmission and implement One Health strategies. The research shows that a complex web of interrelated causes is causing zoonotic illnesses to emerge at the wildlife-livestock interface. There are many different sources of infections in livestock and poultry, from well-organized agricultural systems to wildlife reservoirs. The interdependence of these ecosystems presents zoonotic concerns that affect populations of animals and cattle alike. The relevance of bacterial and viral zoonoses in the context of wildlife-livestock systems is highlighted by the elucidation of disease transmission mechanisms. Here, we offer mitigation techniques for the danger of targeted diseases emerging or reemerging to stop epidemics in the future.